Development of reliability-centered maintenance model using linguistic failure mode and effect analysis - Mohammed Ahmed Qaid, Alrifaey Moath (2019)
The oil and gas industry is looking for techniques to accurately identify and prioritize the failure modes (FMs) of the equipment and precisely determine the proper maintenance policy and schedule for the failure prevention and reliability satisfaction. Failure mode and effect analysis (FMEA) is an essential tool used in the maintenance approach for the prevention of malfunctioning of the equipment. Moreover, Reliability Centered Maintenance (RCM) is a methodology to choose what maintenance activities have to be performed to keep the asset working within its designed function.